Implement wrist-worn PPG and SpO2 monitoring system - Hong Noh, Yun; Yun Seo, Ji; Un Jeong, Do (International Journal of Engineering and Technology, 2018)
Background/Objectives: With the advent of an aging society, the advent of smartphones is changing the paradigm of medical services.Existing health care has been aimed at diagnosing and curing, but now there is a lot of focus on personal health monitoring and disease prevention.The PPG signal reflecting the activity state of the heart among the various biological information of the human body has a regular period and regular characteristic.In addition, it is possible to observe pathological and physiological abnormalities by observing changes in the components of the PPG signal according to the state of health and the body, and it can be utilized for diagnosis of heart disease.Methods/Statistical analysis: In this research, we implemented a wrist - worn measuring system to monitor PPG and SPO2 in real time in daily life. Adaptive filter method was applied formotion-artifact removal of PPG and SpO2 signal measured in everyday life. A smart phone application applied the adaptive filter method can monitoring the measured physical information in real time.Findings: For the performance evaluation, the PPG signal of the wrist wearing type measurement system implemented using the commercial PPG measuring device ubpulse 360 (Laxtha, Korea) were comparative evaluation. Also, we measured PPG signals according to activity and rest state in 9 college students. As a result of the experiment, it was confirmed that the mean correlation coefficient between the implemented system and the commercial system was 0.934. We confirmed that the measured results are very similar, and we can confirm the usefulness of the implemented system.Improvements/Applications: In non-invasive SpO2 devices, even with slight movement, the noise is larger than the signal and the ratio of absorbance is incorrectly calculated when calculating SPO2. Therefore, it is difficult to obtain a normal waveform. In order to overcome these disadvantages, we implemented the PPG and SPO2 measurement monitoring system which minimizes the distortion of the PPG signal using the adaptive filter.In the future, we will research techniques for measuring PPG and SPO2 more conveniently in daily life and algorithms for improving the accuracy of PPG data.Â Â